2021
DOI: 10.1007/s00253-021-11710-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Saccharomyces cerevisiae in a concentrated spent sulphite liquor waste stream for increased inhibitor resistance

Abstract: The fermentation of spent sulphite liquor (SSL) from the pulping of hardwoods is limited by the combination of xylose, the primary fermentable sugar and high concentrations of microbial inhibitors that decrease the yeast fermentation ability. The inhibitor resistance phenotypes of xylose-capable Saccharomyces cerevisiae strains were therefore enhanced by combining rational engineering for multi-inhibitor tolerance, with adaptation in concentrated hardwood SSL as selective pressure. The adapted strains were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Currently, sulfite liquor waste streams from wood pulping processes are the only lignocellulosic streams available in the volumes needed to support the tonnage scale of industrial Saccharomyces production. Recent research has shown that molecular engineering coupled with environmental adaptation can deliver S. cerevisiae strains that grow on, and ferment spent sulfite liquors from hardwoods [72,73]. At this stage, we envisage that lignocellulosic substrates would be useful in producing yeast biomass where yeast is being applied in the manufacture of nonpotable ethanol or animal feed applications, but its immediate role in the production of yeast for baking or potable alcohol might be more contentious.…”
Section: Consideration Of Microbial Functions In Lignocellulosic and ...mentioning
confidence: 99%
“…Currently, sulfite liquor waste streams from wood pulping processes are the only lignocellulosic streams available in the volumes needed to support the tonnage scale of industrial Saccharomyces production. Recent research has shown that molecular engineering coupled with environmental adaptation can deliver S. cerevisiae strains that grow on, and ferment spent sulfite liquors from hardwoods [72,73]. At this stage, we envisage that lignocellulosic substrates would be useful in producing yeast biomass where yeast is being applied in the manufacture of nonpotable ethanol or animal feed applications, but its immediate role in the production of yeast for baking or potable alcohol might be more contentious.…”
Section: Consideration Of Microbial Functions In Lignocellulosic and ...mentioning
confidence: 99%